The Effect of Class Management and Work Motivation on The Performance of Public Elementary School Teachers in Pulai Beringin District, Sout Oku Regency - Amidawati, Hisnah; Arafat, Yasir; Yan, Alhadi (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to determine and analyze the effect of classroom management and work motivation partially or jointly on the performance of public elementary school teachers in Pulau Beringin District, South OKU Regency. This research uses quantitative methods. Data were analyzed using multiple linear regression. This study resulted in the conclusions 1) Classroom management affects the performance of public SD teachers in Pulau Beringin District, South OKU Regency; 2) Work motivation affects the performance of SD Negeri teachers in Pulau Beringin District, OKU Selatan Regency; and 3) Class management and work motivation together have a significant effect on the performance of public elementary school teachers in Pulau Beringin District, South OKU Regency. The magnitude of the influence of all independent variables on the performance of SD Negeri teachers in Pulau Beringin District is 92.4%, the remaining 7.6% is influenced by other variables not examined in this study